Seed performance of different corn genotypes during storage - Tathiana Silva Timóteo; Julio Marcos-Filho (Journal of Seed Science)
Corn seed producers have shown significant concern about variations in the seed storage potential of different hybrids, which may not perform as desired. The objective of this research was to evaluate the effect of storage conditions on the physiological potential of seeds of different corn genotypes. Three experimental corn hybrids, each represented by three seed lots produced by Syngenta Seeds, were evaluated. Seeds were stored for fifteen months under three environments: cold and dry chamber (10 ºC and 30% relative humidity), laboratory environment, and controlled sub-optimal environment (20 ºC and 70% relative humidity). Seed performance was evaluated every three months by germination, accelerated aging and cold tests. Activity of the catalase, alcohol dehydrogenase and α-amilase enzymatic systems was also determined using electrophoresis. The storability of corn seeds from different genotypes can be consistently evaluated by associating germination and vigor test results with isoenzymatic activity. Storage under controlled sub-optimal temperature and relative humidity is an efficient procedure to provoke differences in intensity and speed of deterioration in corn seeds of different genotypes.